2019
DOI: 10.1111/1759-7714.13097
|View full text |Cite
|
Sign up to set email alerts
|

CBLL1 is highly expressed in non‐small cell lung cancer and promotes cell proliferation and invasion

Abstract: Background Studies have shown that E3 ubiquitin ligase CBLL1 plays multiple roles in development and tumorigenesis. CBLL1 is over‐expressed in colon cancer and associated with cancer cell proliferation. While, the overexpression of CBLL1 inhibited the estrogenic dependent cell proliferation and migration in ER alpha dependent breast cancer cell MCF‐7. Methods We used an immunohistochemical method to detect CBLL1 expression in human NSCLC and corresponding normal lung ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
(84 reference statements)
3
27
2
Order By: Relevance
“…Next, CBLL1 was predicted and confirmed as a target of miR-545-3p through Targetscan software and dual-luciferase reporter assay, respectively. CBLL1 was up-regulated in NSCLC and breast cancer [18,19,30]. Consistent with the previous studies, we found that the expression of CBLL1 was elevated in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Next, CBLL1 was predicted and confirmed as a target of miR-545-3p through Targetscan software and dual-luciferase reporter assay, respectively. CBLL1 was up-regulated in NSCLC and breast cancer [18,19,30]. Consistent with the previous studies, we found that the expression of CBLL1 was elevated in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating articles have reported the role of CBLL1 in NSCLC. Hui et al found that the expression of CBLL1 was higher in NSCLC, and it facilitated the growth and motility of NSCLC cells [18]. Qui et al reported that XIST accelerated the proliferation and metastasis of NSCLC cells via acting as a miR-212-3p sponge and up-regulating CBLL1 [19].…”
mentioning
confidence: 99%
“…HSP90 is required for the stability and function of numerous oncogenic proteins, and its specific inhibitors display multiple anticancer effects [30][31][32]. On the other hand, Hakai is considered an oncogenic protein that was reported to be overexpressed in various cancers such as colon and lung cancer [16,19,20], furthermore, Hakai knockdown inhibits cell migration [33]. Therefore, we decided to test whether Hsp90 geldanamycin inhibitor may indeed influence the migratory effect driven by Hakai.…”
Section: Downregulation Of Hakai May Partially Account For the Pharmamentioning
confidence: 99%
“…The overexpression of CBLL1 promotes the cell cycle transition of G1-S, which leads to cell proliferation and invasion. Interfering with the expression of CBLL1 gene inhibits cell invasion by increasing the expression of adhesion proteins, and reduces the expression of MMP2 and MMP9 in cells [2,3]. Compared with healthy human colon tissue, Hakai is highly expressed in adenoma and colon adenocarcinoma, and is related to patient stage.…”
Section: Introductionmentioning
confidence: 99%